Understanding University Students’ Green Purchase Behaviour - Lu, Dan; Qiu, Yunxiu; Zhang, Xue; Lu, Jiang (Asia Pacific Economic and Management Review, 2025)
In recent years, universities have increasingly been treated as everyday laboratories for greener lifestyles, yet the link between what students say about the environment and what they actually buy is still quite uncertain. This study applies the Theory of Planned Behaviour to examine how Subjective Norms and Perceived Behavioural Control are connected to Green Consumption Attitude, Green Buying Intention and Green Purchase Behaviour among university students in China. Based on 181 valid questionnaires and analyses conducted with PROCESS Model 6, the findings suggest that both Subjective Norms and Perceived Behavioural Control are linked to more positive attitudes toward green consumption and higher levels of purchase intention. Green Buying Intention is found to be the most stable predictor of behaviour, whereas Green Consumption Attitude alone neither shows a significant direct effect nor serves as an effective single mediator. In most cases, the two predictors influence behaviour through a stepwise route in which changes in attitude are followed by shifts in intention and, only after that, by actual purchasing. This sequential pattern underlines the importance of intention in explaining why supportive environmental views do not always lead to consistent green actions, and it provides a basis for universities, public agencies and businesses to design more targeted measures that make green choices easier and more attractive for students.